Biomechanics of paddling - Baker, J. (ISBS - Conference Proceedings Archive (Konstanz), 2012)
Sprint kayaking performance is based around the simple premise of maximising propulsive forces while minimising drag forces. In a race it is an uncomplicated matter of whoever crosses the line first, i.e. has the highest average velocity, wins. Underlying these straightforward foundations is a number of complex mechanical interactions. Included in these are hydrodynamic drag and propulsion; force development and technique of the paddler; and interplay of the paddler and kayak. Added to this are the kayak classes of K1, K2, and K4 where in the multi-person craft the mechanical system gains further complexity. This presentation will explain the practical implications of the influences on mechanical system and from there outline various methods to evaluate paddling technique and performance with practical application of these analyses.